THE ROLE OF ACALYPHA INDICA LINN. EXTRACT ON HEART RATES WITH MYASTHENIA GRAVIS RAT MODEL - Krisnamurti, Desak Gede Budi; Hakim, Rani Wardani; Antarianto, Radiana Dhewayani; Farida, Siti; Purwaningsih, Erni Hernawati; Purba, Jan Sudir (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: Myasthenia gravis (MG) is an autoimmune disease of the neuromuscular junction (NMJ) caused by antibodies that attack components of the postsynaptic membrane, impair neuromuscular transmission, and lead to weakness and fatigue of skeletal muscle. Acetylcholine is also used as a neurotransmitter in the autonomic nervous system. Striated cardiac muscle can be a target for immune attack manifesting as heart failure, arrhythmia, and sudden death. Involvement of the heart rate (HR) has been claimed and reported, but a causal connection between MG and altered cardiac function has not been found. Methods: For this study of experimental autoimmune MG (EAMG) is used rocuronium, prostigmine, and Acalypha indica (AI) Linn. compared with HR. Results: From the results, the study found that sympathetic activity of HR variability in EAMG injected with rocuronium 10 mg/kg body weight (BW) in 10 min significantly found increasing in measures of short-term variations in HR variability, indicating parasympathetic impairment. Conclusion: We conclude that in MG, cholinergic transmission is affected more diffusely than previously thought. Furthermore, AI was given orally 30 mg/kg BW has an effect similar to the injecting of prostigmine 10 mg/kg BW that can reduce HR. Driven by the fact that the pharmacological treatment of MG is unsatisfied, it needs the therapeutic development for MG using herbal ingredients of AI. This means that the AI compositions containing anti-MG whose composition should be investigated for the next research.